PERJAMUAN TERAKHIR DAN EKARISTI GEREJA - Rahawarin, Bernard A. (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2017)
The Eucharistic Celebration which is performed by the Church up to now, is the fulfilment of Jesus’ commandment: “Do this in memory of Me” (Lc 20:19). Consequently, in obedience to this command, the ecclesiastical celebration of the Eucharist should entail the whole essence which is contained in Jesus’ action, together with his disciples, during the Last Supper, as is described in the New Testament of the Bible. This essence includes the elementary basics, both ritually and ontologically. Thus the eucharist as it is celebrated by the Church as a representation, always participates in Jesus’ Last Supper as its model.